ENHANCING STUDENT ENGAGEMENT IN ISLAMIC CULTURAL HISTORY USING ZEP QUIZ AT MA DARUL ULUM WARU, SIDOARJO - Zahro Nur Laili Hanifah; Agus Darmawan; Zaini Tamim AR (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2026)
Abstract: The rapid development of digital technology has demanded innovation in Islamic Religious Education (PAI), particularly in the subject of Islamic Cultural History (SKI), which is often perceived as monotonous and less engaging, resulting in low student participation. This study aims to analyze the effectiveness of the online educational game Zep Quiz in enhancing students’ activeness and understanding of Islamic values at MA Darul Ulum Waru. The research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving the SKI teacher, students, the Vice Principal for Curriculum Affairs, and the principal. The findings indicate that the implementation of Zep Quiz created a more interactive, participatory, and enjoyable learning environment. Students’ activeness increased through engagement in competitive quiz activities, group discussions, and more enthusiastic responses to the material. In addition to improving cognitive understanding, the use of the educational game facilitated the internalization of values such as perseverance, exemplary conduct, and Islamic spirit. Despite technical challenges, including internet connectivity and limited devices, this innovation is considered relevant to the characteristics of digital-native learners. The author argues that integrating online educational games into PAI instruction represents an effective and contextual pedagogical strategy to enhance learning quality in the digital era. Keywords: online educational games, PAI learning innovation, digital era, and Zep Quiz